2005
DOI: 10.1038/sj.bmt.1705119
|View full text |Cite
|
Sign up to set email alerts
|

Myeloablative conditioning is well tolerated by older patients receiving T-cell-depleted grafts

Abstract: Summary:Older age has been linked to increased transplant-related mortality from graft-versus-host disease (GvHD). Depletion of T cells from stem cell grafts seems to protect from complications of GvHD particularly in older patients. After myeloablative conditioning, patients with haematological malignancies received allogeneic grafts from HLA identical siblings. For GvHD prophylaxis, PBPC grafts were treated ex vivo with anti-CD52, and therapeutic doses of cyclosporin until day þ 90. Survival of patients youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Several studies have demonstrated the efficacy of TCD allogeneic bone marrow (BM)1-3 and TCD peripheral blood stem cell transplants (PBSCT)4,5 from matched related donors (MRD) in patients with hematologic malignancies. In these reports, reduction in the incidence and severity of acute and chronic GVHD, compared with T-cell replete transplantation, has not compromised the anti-tumor effect of the allograft.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of TCD allogeneic bone marrow (BM)1-3 and TCD peripheral blood stem cell transplants (PBSCT)4,5 from matched related donors (MRD) in patients with hematologic malignancies. In these reports, reduction in the incidence and severity of acute and chronic GVHD, compared with T-cell replete transplantation, has not compromised the anti-tumor effect of the allograft.…”
Section: Introductionmentioning
confidence: 99%
“…24 Stem-cell-rich products were incubated at a concentration of 1 mg alemtuzumab/10 10 mononuclear cells 'in the bag' and allowed to react at 20 1C for 30 min. 12,13 Without further manipulation the cell suspension containing the Ab was then infused i.v. in sets devoid of any filters.…”
Section: Treatment With Moab and Gvhd Prophylaxismentioning
confidence: 99%
“…11,12 Indeed, experience has revealed that with this approach the reduced incidence and severity of GVHD has been associated with improvement in the early outcome after transplantation. However, in AA this strategy has been associated with higher incidence of graft failure, but it could be overcome by more powerful immunosuppression during conditioning and by restricting the transfusion of blood products to prevent allosensitization.…”
Section: Introductionmentioning
confidence: 99%
“…Although 1 of these patients required DLI for delayed rise of chimerism, the remainder experienced no significant posttransplantation problems, with no GVHD and a low rate of CMV reactivation (4 of 30), and all patients survived with normal blood parameters. We have previously shown that in the absence of GVHD, older age has little detrimental effect on SCT outcomes, including patients receiving myeloablative therapy for hematologic malignancies [20].…”
Section: Discussionmentioning
confidence: 99%